2020
DOI: 10.1186/s12877-020-01561-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of loneliness and association with depressive and anxiety symptoms among retirees in Northcentral Nigeria: a cross-sectional study

Abstract: Background: Retirees face numerous challenges, including disassociation from persons in their social networks in Nigeria. Perceived social isolation or loneliness could impair the quality of life in old age, and lead to mental disorders. However, it is uncertain whether perceived loneliness has an independent association with depressive and anxiety symptoms and comorbid conditions in Nigerian retirees. Therefore, we aimed at examining the association between perceived loneliness, depressive and anxiety symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 56 publications
6
42
1
2
Order By: Relevance
“…This finding can be explained by the age of the participants in this study. The age over 75 years old is associated with a higher risk of developing depression [ 73 ]; however, only two study participants were aged over 75. Linnea et al confirmed a lower prevalence of depression among younger elderly (60–66 years old), and its increase with age, notwithstanding the level of severity of depression [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding can be explained by the age of the participants in this study. The age over 75 years old is associated with a higher risk of developing depression [ 73 ]; however, only two study participants were aged over 75. Linnea et al confirmed a lower prevalence of depression among younger elderly (60–66 years old), and its increase with age, notwithstanding the level of severity of depression [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings may relate to many factors including differences in social isolation, social support and financial stability ( Cacioppo et al, 2014 ; Holt-Lunstad et al, 2015 ; Petitte et al, 2015 ). Some data suggest a link between loneliness and anxiety ( Igbokwe et al, 2020 ), though there is little research on the relationship between social isolation and anxiety. Especially considering extended social isolation across the world due to the COVID-19 pandemic, this is an issue that may gain even more salience in protecting the mental health of the country ( Elran-Barak and Mozeikov, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, we reported studies that have investigated old-age loneliness using either qualitative (OJEMBE & KALU 2018;OJEMBE & KALU 2019) or quantitative approaches (IGBOKWE et al 2020;OJAGBEMI & GUREJE 2019). However, a mixedmethod approach adopted by the current study as well as the implication for social workers justifies its importance.…”
Section: Introductionmentioning
confidence: 99%